2009
DOI: 10.1055/s-0028-1109176
|View full text |Cite
|
Sign up to set email alerts
|

Increased Duodeno-Gastro-Esophageal Reflux (DGER) in Symptomatic GERD Patients with a History of Cholecystectomy

Abstract: Zusammenfassung ! Grundlagen: Der duodeno-gastro-ösophageale Reflux (DGER) wird als unabhängiger Risikofaktor für die Entstehung einer komplizierten gastro-öso-phagealen Refluxerkrankung (GERD) angesehen. Sowohl klinische als auch epidemiologische Daten lassen vermuten, dass eine Cholezystektomie (CCE) das Ausmaß eines DGER beeinflussen könnte. Methoden: 132 Patienten (67 Frauen, 65 Männer, Altersmedian 55) mit typischen klinischen Beschwerden einer GERD wurden in die Studie eingeschlossen. Die Patienten wurde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The increased and continuous bile flow into the duodenum can either reflux back into the stomach and oesophagus or proceed cephalad down to the small and large bowel. Increased duodenogastro-oesophageal reflux after cholecystectomy is controversial [74][75][76] and probably relates to the method of measurement [76] . The effects of refluxed bile may be augmented by additional noxious refluxed material such as acid and pancreatic enzymes [77] .…”
Section: Proposed Mechanisms Of Carcinogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…The increased and continuous bile flow into the duodenum can either reflux back into the stomach and oesophagus or proceed cephalad down to the small and large bowel. Increased duodenogastro-oesophageal reflux after cholecystectomy is controversial [74][75][76] and probably relates to the method of measurement [76] . The effects of refluxed bile may be augmented by additional noxious refluxed material such as acid and pancreatic enzymes [77] .…”
Section: Proposed Mechanisms Of Carcinogenesismentioning
confidence: 98%
“…Six studies (4 case-control; 2 cohort) demonstrated a positive association between proximal colon cancer and cholecystectomy [59,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79] . An extremely high association (OR = 5.85, 95%CI: 2.13-16.7) was found in one particular Chinese study but 95%CIs were broad and a low quality assessment score indicates these findings are somewhat unreliable [62] .…”
Section: Proximal Colon Cancermentioning
confidence: 99%
“…20 Studies have shown that esophageal reflux is more common in cholecystectomy patients than in control population and it is suggested that duodeno-gastric reflux may play a significant role in the pathogenesis of PCS. 4,15,21 However, other studies shows contrary results. Lin et al compared pre-and postcholecystectomy changes in reflux symptoms in a large controlled prospective observational study.…”
Section: Discussionmentioning
confidence: 45%
“…4,5 However, there are also studies, which shows no change. 6,7 In 1991, Silny was the first investigator who described multichannel intra-luminal impedance (MII), a technique which detects intra-esophageal bolus transport by measuring the resistance to alternating current (i.e., impedance) of the content of the esophageal lumen.…”
Section: Tropical Gastroenterology 2014;35(4):222-226mentioning
confidence: 99%
“…Since confounding cannot be ruled out as an explanation for the association between gastrectomy and laryngeal or pharyngeal cancer, it is valuable to address exposure to bile reflux in relation to these tumors also using other approaches. Cholecystectomy for gallstones offers such possibility, since it is followed by an increased level of bile in the gastric juice due to a continuous flow of bile to the duodenum, and patients with reflux who have undergone cholecystectomy have an increased bile acid presence in the esophagus 8. Moreover, cholecystectomized patients have an increased risk of developing esophageal adenocarcinoma, which may be explained by bile salts 9, 10.…”
mentioning
confidence: 99%